SMALL BUSINESS GROWTH IN THE CONTEXT OF TOURISM - Drakulevski, LJubomir; Janeska iliev, Aleksandra (Faculty of Economics University of East Sarajevo, 2018)
The discussion evolves around the concept of small business considering specific characteristics and especially external factors influencing their performance,more specifically their growth. Analysis related to small business have noticeably grown in the last twenty years,being for a long time out shined by the global dominance of large businesses operations. The huge presence of small businesses in any economy provides a basis for reviewing various aspects related to their operations. In terms of the increasing importance of small business for the recovery and growth of world economy, the characteristics of small businesses are relevant and important research areas. Small businesses have been considered to be dominant in areas where conducting business is strongly influenced by tourism.This paper is oriented strongly towards the issues and settings of small business with a focus on those situated in the touristic region of Ohrid, Macedonia. Hence the purpose of this research effort is to determine whether the growth of small businesses is influenced by different aspects,especially the regional aspect of being active in a touristic region. The empirical research includes 89 companies from the most prominent touristic destination in Macedonia, the city of Ohrid. A multiple regression analysis is used or a empirical point including multiple independent variable an done dependent variable reflecting various aspects of the proposed discussion focusing around growth and tourism.
Keywords: characteristics, small business, tourism, growth.